Arsenic and Mercury Distribution in an Aquatic Food Chain: Importance of Femtoplankton and Picoplankton Filtration Fractions. (9th December 2022) - Alowaifeer, Abdullah M.; Clingenpeel, Scott; Kan, Jinjun; Bigelow, Patricia E.; Yoshinaga, Masafumi; Bothner, Brian; McDermott, Timothy R.
Abstract: Arsenic (As) and mercury (Hg) were examined in the Yellowstone Lake food chain, focusing on two lake locations separated by approximately 20 km and differing in lake floor hydrothermal vent activity. Sampling spanned from femtoplankton to the main fish species, Yellowstone cutthroat trout and the apex predator lake trout. Mercury bioaccumulated in muscle and liver of both trout species, biomagnifying with age, whereas As decreased in older fish, which indicates differential exposure routes for these metal(loid)s. Mercury and As concentrations were higher in all food chain filter fractions (0.1‐, 0.8‐, and 3.0‐μm filters) at the vent‐associated Inflated Plain site, illustrating the impact of localized hydrothermal inputs. Femtoplankton and picoplankton size biomass (0.1‐ and 0.8‐μm filters) accounted for 30%–70% of total Hg or As at both locations. By contrast, only approximately 4% of As and <1% of Hg were found in the 0.1‐μm filtrate, indicating that comparatively little As or Hg actually exists as an ionic form or intercalated with humic compounds, a frequent assumption in freshwaters and marine waters. Ribosomal RNA (18S) gene sequencing of DNA derived from the 0.1‐, 0.8‐, and 3.0‐μm filters showed significant eukaryote biomass in these fractions, providing a novel view of the femtoplankton and picoplankton size biomass, which assists in explaining why these fractions may contain such significant Hg and As. These results infer that femtoplankton and picoplankton metal(loid) loads represent aquatic food chain entry points that need to be accounted for and that are important for better understanding Hg and As biochemistry in aquatic systems. Environ Toxicol Chem 2023;42:225–241. © 2022 SETAC